AImagery: A Multisensory Approach to Anxiety Reduction with AI, Olfactory Stimuli, and Biofeedback-Enhanced Guided Imagery - Amores, Judith; Hernandez, Javier (2024 Affective Computing and Intelligent Interaction, 2024)
We present AImagery, an AI-powered immersive relaxation experience tailored to user preferences and physiological feedback. In a study with 32 participants, half of them experienced a multisensory experience with scent, biofeedback, and a personalized AI audio story based on their heart rate, self-reported mood and custom scenery. The experimental group showed a significant anxiety reduction for those with moderate to high anxiety, as opposed to the control group (non-guided meditation/baseline resting control condition). User feedback was positive and received high ratings for enjoyment, immersion and, to a lesser extend, sleepiness. Our results highlight the potential of multisensory AI-driven relaxation tools for those with elevated anxiety.